2021
DOI: 10.1029/2020gl092194
|View full text |Cite
|
Sign up to set email alerts
|

Californian Wildfire Smoke Over Europe: A First Example of the Aerosol Observing Capabilities of Aeolus Compared to Ground‐Based Lidar

Abstract: In September 2020, extremely strong wildfires in the western United States of America (i.e., mainly in California) produced large amounts of smoke, which was lifted into the free troposphere. These biomass-burning-aerosol (BBA) layers were transported from the US west coast towards central Europe within 3-4 days turning the sky milky and receiving high media attention. The present study characterises this pronounced smoke plume above Leipzig, Germany, using a ground-based multiwavelength-Raman-polarization lid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…Although, recent studies suggest that deposition ice nucleation can be the result of pore condensation freezing, where homogeneous ice nucleation occurs at lower supersaturation in nanometersized pores (David et al, 2019;Marcolli, 2014). When the supercooled smoke particle takes up water or its shell deliquesces, immersion freezing can proceed, where the INP immersed in an aqueous solution can initiate freezing (Knopf et al, 2018;Berkemeier et al, 2014). Finally, if the smoke particle becomes completely liquid (and no insoluble part within the particle is left), homogeneous freezing will take place at temperatures below 235 K (Koop et al, 2000).…”
Section: Cloud-relevant Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, recent studies suggest that deposition ice nucleation can be the result of pore condensation freezing, where homogeneous ice nucleation occurs at lower supersaturation in nanometersized pores (David et al, 2019;Marcolli, 2014). When the supercooled smoke particle takes up water or its shell deliquesces, immersion freezing can proceed, where the INP immersed in an aqueous solution can initiate freezing (Knopf et al, 2018;Berkemeier et al, 2014). Finally, if the smoke particle becomes completely liquid (and no insoluble part within the particle is left), homogeneous freezing will take place at temperatures below 235 K (Koop et al, 2000).…”
Section: Cloud-relevant Propertiesmentioning
confidence: 99%
“…However, in reality, at given air mass lifting conditions, the ice nucleation process can be very complex. The time that solid OM needs for transition to a more liquid state, termed as humidity-induced amorphous deliquescence, can range from several minutes to days at temperatures low enough for ice formation (Mikhailov et al, 2009;Berkemeier et al, 2014;Knopf et al, 2018). Thus the phase change (as function of T and RH) can be longer than typical cloud activation time periods (governed by the updraft velocity), potentially inhibiting full deliquescence and allowing the OA or the organic coating to serve as INP.…”
Section: Cloud-relevant Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Particulate matter measurements from ground stations stations in the Western U.S. registered extended exceedances during the 9 d period (figure S3(A)), leading to extreme exposures over Oregon and Washington (figure S3(B)) for several vulnerable populations (supplementary information). The smoke plumes were observed as far away as Leipzig, Germany on 11 September, where co-located ground-based and spaceborne lidars sampled the biomass burning aerosol that were lofted into the free troposphere [5], likely due to intense convection associated with cumulonimbus flammagenitus, or pyrocumulonimbus [21]. Moreover, the High-Resolution Rapid Refresh (HRRR) Smoke modeling system (https://rapidrefresh.noaa.gov/hrrr/HRRRsmoke/) predicted smoke plume transport within the U.S. reasonably well during this period (not shown).…”
Section: The Western Us Wildfires Of 2020mentioning
confidence: 99%
“…The Aeolus optical properties product started to be used in validation studies (e.g. Baars et al, 2021), which showed it could provide valuable data. Finally, assimilation of the Aeolus backscatter coefficient into atmospheric chemistry and transport models is being studied and first results are encouraging (Letertre-Danczak et al, 2021).…”
Section: Discussionmentioning
confidence: 99%